Effect of O-chitosan nanoparticles on the development and membrane permeability of Verticillium dahliae. (1st June 2017) - Xing, Ke; Liu, Yuanfang; Shen, Xiaoqiang; Zhu, Xiao; Li, Xiaoyan; Miao, Xiangmin; Feng, Zhaozhong; Peng, Xue; Qin, Sheng
Highlights: O-chitosan nanoparticles dramatically decreased the mycelium growth of V. dahlia . The spore germination rate and dispersion state was changed with nanoparticles-treated. Electron microscopy measurements demonstrated degenerative alterations of V. dahlia . O-chitosan nanoparticles were internalized by spores and mycelium. The increase of release of intracellular components and decrease of cellular protein evidenced the damaged membranes. Abstract: Verticillium dahliae, which causes wilting in over 300 woody and herbaceous plant species, is a representative of fungal plant diseases for which effective controls are still needed. In this study, the antifungal action of oleoyl-chitosan nanoparticles was investigated against V. dahliae . Media containing oleoyl-chitosan nanoparticles dramatically decreased the mycelium growth. The highest antifungal indexes were observed on media amended with 2 mg/mL nanoparticles. Optical microscopy showed that spore germination and hyphae morphology were affected. Scanning electron microscopy and transmission electron microscopy demonstrated degenerative alterations including crumpled hyphae and spores, thickened cell walls, disappeared membranous organelles, massive vacuolation of the cytoplasm, and cell wall-plasmalemma separation. Fluorescence microscopy showed that nanoparticles were internalized by fungal cells. The sharp increase in the release of intracellular components and decrease of total cellular protein concentration demonstrated damaged cell membranes. Overall, the results indicate that oleoyl-chitosan nanoparticles have the potential to control phytopathogens in agriculture.